Studi Financial Statement Fraud dengan Fraud Triangle Theory - Chandrawati, Novalia Budi; Dyah Ratnawati (STEKOM PRESS, 2021)
The purpose of this study is to examine influence of financial stability, external pressure, nature of industry, and rationalization to financial statement fraud. The sample used in this study is manufacture companies listed on the Indonesia Stock Exchange (BEI)in the period 2018-2019. By using purposive sampling method, it is obtained as many as 77 mnufacture companies as the study sample. The method of analysis used in this study is logistic regression. In this research include overall fit model test, hosmed and lemeshow test, goodness of fit test, and classification matrix result of this study indicate that the financial stability is significant to financial statement fraud, while external pressure, nature of industry, and rationalization are not significant to financial statement fraud